Responsibility for Village Financial Management in Dutuno Village, Paleleh District, Buol Regency based on Permendagri - Muhammad Nur Iman Odja (Estudiante Law Journal, 2023)
The purpose of this study was to determine the accountability of Village Financial Management in Dutuno Village, Paleleh District, Buol Regency according to Permendagri No. 20 of 2018. This study uses empirical research methods with a qualitative approach. The results of this study, namely village financial management accountability is a problem until now in Dutuno Village, Paleleh District, Buol Regency, because the village government is not open to the public in terms of informing village financial management accountability reports in accordance with Permendagri No. 20 of 2018 on Village financial management accountability in Dutuno Village, Paleleh District, Buol Regency, of course, this a problem when the accountability of village financial management is not carried out according to applicable rules.